Apologetics in Africa: An Introduction - Ndereba, Kevin Muriithi (HippoBooks, 2024)
This textbook provides an in-depth exploration of the biblical, philosophical, cultural, and practical concerns facing African Christians as they proclaim and defend the gospel in Africa. Written by a diverse group of pastors and scholars, it provides a much needed interdisciplinary and contextualized approach to apologetics.
paid